THE EFFECT OF GENDER VIOLENCE ON HUMAN RIGHT IN SOUTH SUDAN - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
According to the United Nations General Assembly (2013), gender based domestic violence involves men and women and usually results in physical, sexual, or psychological harm or suffering to the victims. It also includes threats of such acts, coercion or arbitrary deprivation of liberty. A study from World Health Organisation (2016) indicates that between 16% and 52% of women worldwide are physically assaulted by an intimate partner at least once in their lives. In addition, according to the Inter-American Development Bank’s special report on domestic violence in 1999, gender based violence results in direct loss of money due to health care, police, court costs and productivity. Besides financial losses, gender based violence has also been identified as a contributory factor to maternal mortality rate by 55 percent (World Bank, 2013). Further, the World Health Organisation in 1996 documented that, among women aged 15-44 years, gender violence often leads to death and disability. In addition, studies in India, Bangladesh, the USA, Papua, New Guinea and Peru indicate a high correlation between domestic violence and suicide rates (WHO, 1997). Statistics published in 1997 by the World Health Organization on studies conducted in 24 countries in America, Europe and Asia revealed that between 20% and 50% of the women interviewed reported that they suffered physical abuse from their male partners. Moreover, according to an international report on the status of women in 140 countries, the number of women reporting physical abuse by a male partner during the period 1986-1993 was 21% to 60% (Neft & Levine, 1997).